The effect of Ni/Al2O3 catalyst mass variation and operation time on the CO2 methanation process - Yongki Pratama; Robert Junaidi; Didiek Hari Nugroho (Universitas Lambung Mangkurat, 2025)
Carbon dioxide (CO2) is one of the biggest contributors to the greenhouse effect. Based on data from the International Energy Agency (IEA), greenhouse gas (GHG) emissions continue to increase, reaching 37.8 billion tons in 2024. One way to reduce carbon dioxide (CO2) is to convert carbon dioxide (CO2) into methane (CH4) through a methanation process using a Fixed Bed Reactor. This study was conducted by varying the mass of Ni/Al2O3 catalyst between 55 grams and 60 grams and the operating time between 90, 100, 110, 120, and 130 minutes, as well as adding 20 grams of Zn promoter to improve catalyst stability performance. A Multi Gas Detector Analyzer was used to analyze the methane (CH4) gas produced. The results of this study showed that the highest percentage of methane gas (CH4) produced was obtained in sample 10 with a Ni/Al2O3 catalyst mass of 60 grams and an operating time of 130 minutes, which was 58.35%.